Exploring of Islamic Religious Education Models in Senior High Schools: Analysis Implementation, Challenges, and Expectations in the Teaching of Moral - Rizal Permana; Edi Suresman; Mokh. Iman Firmansyah; Sodiqov Ulug’bek G’ulomjon O’g’li (Universitas Muhammadiyah Mataram, 2025)
This study investigates the implementation of Islamic Religious Education learning models on moral elements in senior high schools, emphasizing teachers’ and students’ perceptions. Unlike previous studies that focus solely on learning models or moral education, this research uniquely examines the alignment between teacher-implemented models and student expectations, using Joyce and Weil’s learning model framework. Employing a qualitative phenomenological approach, data were collected through in-depth interviews with three PAI teachers in West Bandung Regency and open-ended questionnaires from 120 students. Findings reveal that teachers attempt to integrate structured learning models; however, challenges persist, including variations in student backgrounds, limited teacher comprehension of moral content, and difficulties in classroom management. Students expect learning to be relevant, flexible, interactive, and technology-integrated, yet gaps remain between these expectations and current teaching practices. Key elements of the Joyce and Weil model—syntax, social systems, reaction principles, and support systems—are not comprehensively implemented across the studied schools. This study contributes to the development of PAI learning by offering structured insights into improving instructional models systematically. It recommends targeted strategies for teachers to enhance instructional effectiveness and suggests future research employing a larger sample with a quantitative approach to further validate these findings.